Exploration of Predictive Biomarkers for Postoperative Recurrence in Chronic Rhinosinusitis with Nasal Polyps Based on Serum Multiple-Cytokine Profiling - Gang Wang; Huiyuan Zheng; Xiaoqian Chen; Jing Zheng; Jiabin Zhan; Rui Li; Yanyan Qi; Yi Ye; Min Zeng; Xin Wei (Hindawi Limited, 2022)
Background. Functional nasal endoscopic surgery (FESS) is an effective treatment approach for chronic rhinosinusitis with nasal polyps (CRSwNP) patients, but some patients still suffer from postoperative recurrence. This study is aimed at investigating the expression of multiple cytokines in CRSwNP and revealing their relationships with postoperative recurrence. Methods. A total of 72 patients with CRSwNP, including 36 primary and 36 recurrent patients, were enrolled. Serum samples were obtained, 30 cytokine levels were measured by multiplex analysis, and the association between cytokine levels and recurrence was assessed. The most potential cytokines were further validated in another independent cohort with 60 primary and 60 recurrent CRSwNP patients. Results. The results of multiple cytokine profiling exhibited that the levels of eotaxin, G-CSF, IFN-α, IL-13, IL-17A, IL-5, MCP-1, and RANTES were vastly changed in the recurrent group in comparison with the primary group. Receiver-operating characteristic (ROC) curves highlighted that serum levels of eotaxin, IL-17A, and RANTES were strongly predictive of postoperative recurrence (area under the curve AUC>0.7, P<0.05). Further validation results showed that elevated serum eotaxin, IL-17A, and RANTES levels were enhanced in the recurrent group. The ROC curve showed that serum eotaxin (AUC=0.729, P<0.001) and RANTES (AUC=0.776, P<0.001) exhibited stronger ability than serum IL-17A (AUC=0.617, P=0.027) in predicting CRSwNP recurrence. Conclusion. Our data suggested that serum multiple cytokine profiling was associated with postoperative recurrence of CRSwNP, and eotaxin and RANTES might serve as potential biomarkers for predicting postoperative recurrence. These results might contribute to the understanding of the underlying mechanisms of recurrence and provide novel clues for precision therapy in CRSwNP.